Effects of biochar on growth, and heavy metals accumulation of moso bamboo (Phyllostachy pubescens), soil physical properties, and heavy metals solubility in soil. (March 2019) - Wang, Ying; Zhong, Bin; Shafi, Mohammad; Ma, Jiawei; Guo, Jia; Wu, Jiasen; Ye, Zhengqian; Liu, Dan; Jin, Hexian
Abstract: Pot experiment was conducted to investigate the effects of wood biochar (5%), bamboo biochar (5%), rice straw biochar (5%) and Chinese walnut shell biochar (5%) on growth, accumulation of heavy metals in moso bamboo, soil physical properties, and solubility of heavy metals in soil. The results revealed that dry weight of moso bamboo was significantly increased in treatments of wood biochar (5%), rice straw biochar (5%) and Chinese walnut shell biochar (5%) except bamboo biochar (5%). Application of straw biochar (5%) was most effective in enhancing plants biomass, with increase of 157%, 113% and 111% in leaves, roots and stems of moso bamboo. All treatments of biochar have significantly improved soil electrical conductivity with maximum increase of 360% compared to CK. In case of heavy metals accumulation, application of 5% bamboo biochar, straw biochar and Chinese walnut shell biochar has reduced Cu uptake in roots by 15%, 35% and 26%, respectively. The biochars have significantly reduced solubility of soil heavy metals with maximum reduction of 58.91 mg kg −1 and 10.59 mg kg −1 of Cu and Pb with application of rice straw biochar. It is concluded that dry weight of moso bamboo was significantly enhanced by all treatments of biochar except bamboo biochar. Highlights: Dry weight of moso bamboo was significantly increased in all treatments of biochar except bamboo biochar. Application of 5% straw biochar was most effective in enhancing plants biomass. Application of 5% bamboo biochar, straw biochar and Chinese walnut shell biochar has reduced Cu uptake in roots. Applications of biochar has significantly reduced the solubility of soil heavy metals.